Pengaruh Volume Impor Bawang Putih Terhadap Harga Eceran Bawang Putih di Indonesia - ulfathul arzia; Riyanto Riyanto (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2023)
Garlic import has been carried out by Indonesian government in 2011-2020 because domestic production is only sufficient for about three to five percent of people’s needs. The addition supply of imported garlic in domestic market due to the import policy is expected to reduce garlic retail price. This study aims to examine the effect of garlic import volume on garlic retail price in Indonesia. By using Distributed Lag Model (DL-Model) and Vector Error Correction Model (VECM) with monthly data for Januari 2011 – December 2020, this study shows that the effect of garlic imports volume begins to reduce the retail price of garlic after one month of import implementation. The effect continues to be significant up to 6 months after the import implementation. These results indicate, within a period of one month (short term), the policy of importing garlic has not been able to affect the retail price of garlic. However, in the long term (after one month to 6 months), the policy of importing garlic significantly affects the decline in retail prices of garlic.